2024
DOI: 10.1101/2024.04.05.24305281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serotype-Specific Epidemiological Patterns of Inapparent versus Symptomatic Primary Dengue Virus Infections: A 17-year cohort study in Nicaragua

Sandra Bos,
Jose Victor Zambrana,
Elias Duarte
et al.

Abstract: BackgroundDengue is the most prevalent mosquito-borne viral disease and a major public health problem worldwide. Most primary infections with the four dengue virus serotypes (DENV1-4) are inapparent; nevertheless, prior research has primarily focused on symptomatic infections, which has limited our understanding of the epidemiological burden and spectrum of disease of each DENV serotype. Our study addresses this bottleneck in dengue research by providing a new method and a detailed examination of primary inapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
2
1
Order By: Relevance
“…In the present study, which includes presecondary DENV1, DENV2, and DENV3 infection samples, after performing a stratification analysis by DENV serotype, we found that ADCD was correlated with protection especially in the pre-secondary DENV3 infection sample group, using E and NS1 recombinant antigens. In contrast, we found that nAb titers are more correlated with protection in pre-DENV2 compared to pre-DENV3 infection samples (36), raising the possibility that protection against different DENV serotypes may be associated with different antibody functions. When the ADCD assay was performed with ZIKV E and NS1 antigens, protection was observed when all samples were analyzed together, but not when the analysis was stratified by pre-DENV2 and pre-DENV3 subgroups.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In the present study, which includes presecondary DENV1, DENV2, and DENV3 infection samples, after performing a stratification analysis by DENV serotype, we found that ADCD was correlated with protection especially in the pre-secondary DENV3 infection sample group, using E and NS1 recombinant antigens. In contrast, we found that nAb titers are more correlated with protection in pre-DENV2 compared to pre-DENV3 infection samples (36), raising the possibility that protection against different DENV serotypes may be associated with different antibody functions. When the ADCD assay was performed with ZIKV E and NS1 antigens, protection was observed when all samples were analyzed together, but not when the analysis was stratified by pre-DENV2 and pre-DENV3 subgroups.…”
Section: Discussioncontrasting
confidence: 77%
“…Currently, neutralization assays have been the main method used to assess protection in vaccine trials and natural infection studies, with the caveat that nAb titers do not always correlate with protection from disease in humans. Multiple parameters (e.g., virion maturation state, cell line substrate, infection history, and incoming infecting serotypes) have been shown to affect neutralization assays, highlighting the need to control assay conditions carefully and to develop novel methods to assess protection ( 22 , 36 ). The complex nature of anti-DENV antibodies and the lack of tools to indicate individuals protected from disease have led to major shortcomings in vaccine development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation